Analysis of Passenger Ability and Willingness to Pay for the Surabaya-Yogyakarta Train Route - Ardiansyah, Dhaifan; Widyastuti, Hera (Institut Teknologi Sepuluh Nopember, 2025)
The Directorate General of Railways of the Ministry of Transportation has been constructing double-track railway lines along the southern route of Java since 2015, covering a distance of 694 km This project aims to connect three major agglomeration cities, namely Jabodetabek, Joglosemar (Jogja - Solo - Semarang), and Gerbangkertosusila (Gresik - Bangkalan - Mojokerto - Surabaya - Sidoarjo - Lamongan). PT Kereta Api Indonesia accelerated travel times for several trains using the south of Java double-track railway starting September 24, 2021, as part of service improvements. In line with the construction of the double-track railway and service improvements by the Directorate General of Railways of the Ministry of Transportation and PT Kereta Api Indonesia, ticket/fare rates need to be reviewed, especially if there is an increase in ticket prices for the economy and executive classes, which include the Wijayakusuma, Sancaka, and Mutiara Selatan trains. This research aims to determine passenger characteristics, Ability to Pay (ATP), and Willingness to Pay (WTP) for the services used and to provide alternative scenarios in the event of fare increases to improve service quality. The methods used to address these issues include collecting primary data through interviews and questionnaires, analyzing respondent characteristics, and analyzing willingness and availability to pay using the Stated Preference approach. Subsequently, the Household Budget method and service user perceptions will be employed to obtain ATP and WTP values. The results of this study for the economy class show an Ability to Pay (ATP) value of IDR 307.249 and a Willingness to Pay (WTP) value of IDR 250.593. For the executive class, the ATP value is IDR 396.943, and the WTP value is IDR 277.462.